HUBUNGAN GRAVIDA IBU DENGAN KEJADIAN PREEKLAMPSIA - Sri Sumarni; Syaifurrahman Hidayat; Eko Mulyadi (Fakultas Ilmu Kesehatan, 2014)
Background:Pre-eclampsiaandeclampsiaishypertensioncausedbypregnancycharacterized byhypertension, edema, andProteinuriafterthe 20th week, andifaccompanied byseizuresis calledeclampsia. Cause ofpre-eclampsiariskfactors, namely: the reproductivestatus, health status, andhealthbehaviorsImmunologictheoryexplainsclearlyaboutthe relationshiporgravida,gravidawithpreeclampsiaincidence. The theorystatesblockingantibodies againstplacentalantigensformed atfirstto be the causeof preeclampsiapregnancySubject:to determine the relationshipgravidamotherswithpreeclampsiain dr. H.Moh. AnwarSumenepMethods:Thisstudyis atype ofanalyticalstudyusing aretrospectivecross-sectional approach. Most ofthe samplesin this studywomen withpreeclampsiain dr. H.Moh. AnwarSumenep. Total numberinJanuary andFebruary 2014is 33mothers, with theinclusion and exclusion criteriasamplingtechniqueusingpurposive sampling techniqueForprocessingthe datausingthe completed questionnairesare then processed bystagesincludingEditing, Coding, ScoringandTabulating. Analysis ofthe datausing theChi-squareResults: The majority ofrespondents in thecategorygravidaat riskas much as54.5%, andthe majority ofrespondentsexperiencedpreeclampsia51.5% where the resultsof this studyin accordancewith the theorywhich statesthata woman who hadbecomea motherwitha new partnerat risk ofsix toeighttimesmore susceptible topreeclampsiathanmultigravida. Conclusion:The results ofthe dataanalysisstatistical testChiSquarewiththe resultssig: 0.001(<0.05) whichindicatesthat there is arelationshipGravidaMotherswithPreeclampsiaGenesis Keywords:MotherGravida, Preeclampsia